2009
DOI: 10.1007/s12032-009-9271-3
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of ambroxol on radiation lung injury and influence on production of transforming growth factor β1 and tumor necrosis factor α

Abstract: The aim of this article was to investigate the effect of ambroxol on radiation lung injury and the expression of transforming growth factor beta(1) (TGF-beta(1)), as well as tumor necrosis factor alpha (TNF-alpha) in plasma. Totally, 120 patients with locally advanced lung cancer in radiotherapy were randomized into treatment and control groups. Patients in the treatment group took ambroxol orally at a dosage of 90 mg, three times per day for 3 months from the beginning of radiotherapy. The expression of TGF-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…It was recently reported that irradiated patients with locally advanced lung cancer who received ambroxol treatment exhibited a statistically significant decrease in serum TGF-β1 compared to a control group [42]. Our results support the concept that serum TGF-β1 is a useful parameter for evaluating treatment effects in patients with radiation-induced lung injuries.…”
Section: Discussionsupporting
confidence: 87%
“…It was recently reported that irradiated patients with locally advanced lung cancer who received ambroxol treatment exhibited a statistically significant decrease in serum TGF-β1 compared to a control group [42]. Our results support the concept that serum TGF-β1 is a useful parameter for evaluating treatment effects in patients with radiation-induced lung injuries.…”
Section: Discussionsupporting
confidence: 87%
“…Further studies were published investigating the prevention of pulmonary complications in severely ill patients by ambroxol [28][29][30][31][32][33][34].…”
Section: Lung-protective Propertiesmentioning
confidence: 99%
“…[20] showed that the expression of TGF-β1, as well as TNF-α in plasma did not rise in ambroxol treated lung cancer patients on radiation therapy as compared with the controls. The DLCO was also preserved in the ambroxol treated patients.…”
Section: Ambroxolmentioning
confidence: 99%
“…[1516171819] Even in human studies, the agent was to able to block the expression of TGF-β1 and TNF-α in plasma and preserving the DLCO of the lungs in lung cancer patients on radiation therapy. [20]…”
Section: Ambroxolmentioning
confidence: 99%